Resnikov prekop Najstarejša koliščarska naselbina na Ljubljanskem barju = The oldest pile-dwelling settlement in the Ljubljansko barje - Velušček, Anton (Opera Instituti Archaeologici Sloveniae, 2006)
In the monograph the results of the most recent research of the prehistoric pile-dwelling settlement Resnikov prekop near Ig on the southeastern part of the Ljubljansko barje are presented.